Unconstitutional Legal Problems of the Job Creation Law against Local Working Patents in the Elimination of Article 20 of Law Number 13 of 2016 concerning Patents - Juliani Fransiska (LEGAL BRIEF, 2022)
Patent is a tool or tool aimed at disseminating technology and means in transferring technology so that patents can have a high social impact both through learning and economic progress of society in a country through technological developments. Patents are not only about granting the right to monopolize. However, it is also an award for technology to develop which will eventually have a good impact in the world of education and teaching as well as from the development of technology itself which aims also to increase the economic growth of the community. This method of research is normative juridical. The problem in this study is How is the problem of the application of local working after the abolition of article 20 in the UUPATEN? and then after the validity of Article 110 of the Job Creation Law for almost 1 year How is the polemic of the position of Article 20 of the UUPATEN and the achievement of TRIPs after the unconstitutional occurrence of the Job Creation Law based on the Constitutional Court Decision Number 91 / PUU-XIX / 2021? The conclusion of this study is that Article 20 of the Patent states that Bauwa requires patent holders to make products in Indonesia. So that Article 20 makes a conflict with Article 27 paragraph 1 trips agreement. the ratification of the JOB CREATION Law was then declared conditionally unconstitutional by the constitutional court and resulted in the regulations it had previously invited to patents.